Effects of Megasphaera elsdenii administration on performance and carcass traits of finishing Bos indicus feedlot cattle. Issue 3 (28th May 2021) - Lopes, Ana Laura; Santos, Flávio A P; Meschiatti, Murillo; de Oliveira, Mario Olímpio; Fernandes, Juliano J R; Drouillard, James S; Cappellozza, Bruno I
Abstract: This study evaluated the effects of Megasphaera elsdenii administration at the beginning of the feedlot period on performance of Bos taurus indicus bulls. On d 0, 383 Nellore bulls (initial shrunk body weight 384 ± 29.2 kg; initial age = 24 ± 2 mo) were assigned to treatments in a randomized complete block design. Treatments consisted of 1) 14 d adaptation diet and transition to a finishing diet (CONT ), 2) CONT plus oral administration of 20 mL of Lactipro-NXT ( M. elsdenii ) on d 0 of the study (MEG-14 ), 3) CONT diet, consisting of 6 d of adaptation diet plus oral administration of 20 mL of Lactipro-NXT on d 0 of the study (MEG-6 ), and 4) No adaptation diet and oral administration of 20 mL of Lactipro-NXT on d 0 of the study (MEG-0 ). Experimental period lasted 119 d. No treatment effects were observed for any of the performance parameters evaluated herein ( P ≥ 0.15). Nonetheless, a treatment × wk interaction was observed for DM, NEm, and NEg intakes ( P < 0.0001). For all these parameters, MEG-0 and MEG-6 had a reduced intake vs. MEG-14 and CONT in the first wk of the study ( P ≤ 0.05). For the carcass traits, no effects were observed for HCW ( P ≥ 0.24), whereas MEG-6 had a greater REA when compared with MEG-0 and MEG-14 (quadratic effect; P = 0.04) and MEG-administered bulls tended to have a greater BFT vs. CONT ( P = 0.08). In summary, M. elsdenii administration at the beginning of the feedlot period did not improve performance, whereas reducing the length of the adaptation period for 6 d improved REA of finishing Bos taurus indicus bulls.